2019
DOI: 10.1073/pnas.1721434116
|View full text |Cite
|
Sign up to set email alerts
|

Microglia are effector cells of CD47-SIRPα antiphagocytic axis disruption against glioblastoma

Abstract: SignificanceTumor-associated microglia and macrophages (TAMs) constitute up to one half of the cells in glioblastoma multiforme (GBM) and are known to promote tumor growth. Therefore, modulation and reeducation of the TAM pool is a promising antitumor strategy against GBMs. We recently showed that disruption of the SIRPα-CD47 signaling axis is efficacious against various brain tumors including GBM primarily by inducing tumor phagocytosis. Here, we show that tumor-associated microglia are capable of in vivo tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
186
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(192 citation statements)
references
References 37 publications
5
186
0
1
Order By: Relevance
“…Many tumors are described to overexpress CD47 Zhao et al, 2016). Inhibition of CD47 in a preclinical model showed a modification of microglia phenotypes in GB that was correlated with better survival (Hutter et al, 2019). Furthermore, in vivo, the anti-CD47 treatment is able to shift the macrophage phenotype toward an M1 type and induces anti-tumor effects .…”
Section: Inhibition Of Cd47mentioning
confidence: 97%
“…Many tumors are described to overexpress CD47 Zhao et al, 2016). Inhibition of CD47 in a preclinical model showed a modification of microglia phenotypes in GB that was correlated with better survival (Hutter et al, 2019). Furthermore, in vivo, the anti-CD47 treatment is able to shift the macrophage phenotype toward an M1 type and induces anti-tumor effects .…”
Section: Inhibition Of Cd47mentioning
confidence: 97%
“…The targeting of this axis with humanized anti-CD47 antibodies enhanced tumour phagocytosis and reduced tumour burden in patient-derived orthotopic xenografts of paediatric brain tumours [54]. Interesting results were also obtained using orthotopic xenografts and a syngeneic mouse model with genetically color-coded macrophages (Ccr2 RFP ) and microglia (Cx3cr1 GFP ), in which microglia were found to effectively phagocytose tumour cells in response to anti-CD47 blockade with a reduced inflammatory signature, making them a promising target for clinical applications [55]. Another example highlighting TAM subset-specific facets is the response to the VEGF neutralizing antibody bevacizumab, where blood-derived TAMs, instead of resident microglia, preferentially contributed to therapy resistance [56].…”
Section: Immune Checkpoint Inhibitors and Reprogramming Of Tumour-assmentioning
confidence: 99%
“…Blockade of CD47-SIRPα signaling is intended to promote the ability of myeloid cells, in particular, macrophages (Mφs) to phagocytose tumor cells and induce antitumor responses. 23 Nevertheless, there is substantial evidence that Mφs in the tumor microenvironment could be programmed into an altered phenotype that promotes tumor progression. 17,[24][25][26][27][28][29][30] For example, our previous studies showed that tumoractivated monocytes (Mos)/Mφs secrete cytokines, such as TNFα, IL-1β and IL-6, to enhance tumor cell autophagy and angiogenesis in HCC.…”
Section: Introductionmentioning
confidence: 99%